2019
DOI: 10.15359/ree.23-1.1
|View full text |Cite
|
Sign up to set email alerts
|

Ser mapuche en la universidad: Condiciones de ingreso a la formación inicial docente, La Araucanía

Abstract: This article problematizes social factors that affect the entry to and continuity in higher education of indigenous students who belong to involuntary minority cultures. We advocate the thesis that Mapuche students face personal and social problems that become intercultural tensions whose origin, among other factors, is related to their life before they enter the university. The article aims to describe demographic and academic characteristics, as well as origins, that are particular to Mapuche students of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…The finding related to the perception of verbal violence is linked to ridicule, insults and threats, and this violence can be manifested explicitly or implicitly. The verbal violence perceived by Mapuche students may be related to discriminatory practices exercised by their peers or teachers [82]. In keeping with Ortiz-Velosa et al [82], Mapuche students have historically been the object of stigmatization or ridicule for their school performance, expression of their culture, physical appearance or their last name.…”
Section: Discussionmentioning
confidence: 90%
“…The finding related to the perception of verbal violence is linked to ridicule, insults and threats, and this violence can be manifested explicitly or implicitly. The verbal violence perceived by Mapuche students may be related to discriminatory practices exercised by their peers or teachers [82]. In keeping with Ortiz-Velosa et al [82], Mapuche students have historically been the object of stigmatization or ridicule for their school performance, expression of their culture, physical appearance or their last name.…”
Section: Discussionmentioning
confidence: 90%
“…Poco a poco su sentimiento de seguridad (Bauman, 1997), su constitución del yo (Gergel, 2018) y su propia seguridad personal se verán anuladas sin entender a qué se debería ello. Este proceso ya fue observado por Marx (2004) desde una perspectiva de clase, en donde plantearía que una clase en sí no implica, necesariamente, que sea una clase para sí, es decir, ser consciente de su situación colectiva: "La verdad siempre supe que era mapuche, pero lo que no comprendía es que significaba ser mapuche en Chile o en Santiago porque allá viví mi infancia".…”
Section: Resultsunclassified
“…Furthermore, it will be necessary to consider how financing policies such as cost-free education impact marginalized groups in Chilean society, not only considering their socioeconomic level but also their belonging to specific cultural or ethnic groups, such as indigenous or migrant populations. Although the international experience has shown that access to HEIs has a positive effect on some ethnic groups and social mobility, as observed in the study by Mayeda et al [ 36 ], it will be necessary to analyze what happens with these populations in Chile since the literature has pointed out that groups like the indigenous Mapuche continue to be one of the most vulnerable in the country [ 38 ] .…”
Section: Discussionmentioning
confidence: 99%
“…In the Latin American context and, specifically, in the case of indigenous groups, it has been identified that the Mapuche population continues to maintain low university enrollment rates. In fact, the people of Mapuche origin have been one of the poorest social segments in Chile [ 38 ].…”
Section: Introductionmentioning
confidence: 99%